What is the significance of promoting arts in education for learners with special educational needs today? - Khu, Chooi Ern (2015)
ABSTRACT The arts can be represented in various forms; for example, through painting, music, dance or theatre. This paper seeks to investigate the significance of promoting arts in education for learners with special education needs (SEN). In Chapter 1, readers will be exposed to the rationale behind the chosen topic followed by an illustration of the methodology used for this dissertation in Chapter 2. Chapter 3 to Chapter 5 will consist of literature reviews on (1) the practice of quality art education within schools today; (2) the extent to which arts can be used as a tool to promote inclusion and (3) the impact of the arts in education for learners with SEN. Overall, it was found that findings yielded positive outcomes for the arts to encourage inclusive practices and to assist learners with SEN in the areas of developing self-identify, self-expression, communication, social functioning and motor abilities. Strengths, limitations, future implications and recommendations to improve research in this domain was also identified and described towards the end of this paper. KEYWORDS: arts, education, special education needs